TIR wavelength and emissivity values of select rock samples from the Mourne Mountains, NI - Paul Slezak; Patrick O extquotesingleSullivan; Robbie Ramsay; Michael Stock; Ben Field; Andrea Fagan (PANGAEA, 2023)
The Hyperspectral Analysis of the Mourne Mountains (HAMM) project was undertaken from 2020-2022 in Northern Ireland to integrate spectral, geochemical, and remote sensing data from an exposed, non-arid setting. Mourne Mountain Complex (MMC) samples were obtained by donation from the Geological Survey of Northern Ireland (GSNI) and the Sedgwick Museum (University of Cambridge) as well as from the field by the authors. Samples represent the 5 primary granite types (G1, G2, G3, G4, G5), other minor rock types, and alteration styles. Some sample donations were historic and exact locations unspecified. Their reported coordinates are best estimates from historic literature and projections to surface (see notes in the datasets). A small subset of samples , representing all major rock types and samples of particular interest (e.g. Diamond Rocks), were analysed for thermal infrared (TIR) spectra (i.e. 2.5 to 15 μm) using a Midac M2000 Fourier Transform Infrared open path spectrometer (OP-FTIR) at the NERC FSF, University of Edinburgh. The OP-FTIR was placed within a jig system, which allowed for three blackbody units (2 exttimes2-inch extended area sources, model Infrared Systems Development Corporation IR-2100) to be placed at 90° from the entrance optics of the unit . The blackbody units were set at T1 = 40°C, T2 = 60°C, and Tambient = varying temperature set to ambient conditions and were controlled using an Infrared Systems Development Corporation IR-300 blackbody control unit (uncertainty = ±0.01°C). To convert the raw digital number signal from the FTIR instrument (e.g. the sample) to radiance values, radiometric calibration was conducted by taking measurements of the two blackbody sources at two different temperatures (one below and one above the temperature of the sample) during the measurements and assuming the raw digital number signal is linearly related to the input radiance. The low emissivity, InfraGold standard reference panel and samples were placed on the plate and heated to 50°C. Monitoring of the sample temperature was conducted using a handheld temperature probe.